Treatment of Cornual Pregnancy Combined With Intrauterine Pregnancy Following Embryo Transfer After Bilateral Salpingectomy: Case Report and Review of the Literature - Ji, Xiaowei; Wang, Lin; Zou, Xutong; Peng, Qian; Liu, Suying; Zhu, Jin; Cheng, Haidong; Dong, Xi (Archives of Clinical and Biomedical Research, 2019)
To report a case of treating cornual pregnancy combined with intrauterine pregnancy following embryo transfer after bilateral salpingectomy with a laparoscopic approach. A 40-year-old pregnant woman who presented with minor vaginal bleeding at 5 weeks gestation. A cornual pregnancy with uterine pregnancy by ultrasonography at 7 weeks 4 days gestation was diagnosed. The cornual pregnancy was successfully removed via laparoscopy, and the uterine horn was repaired. The intrauterine single pregnancy progressed and a caesarean section was performed at 37 weeks gestation, resulting in the healthy male infant.